PEMASARAN HIJAU (GREEN MARKETING) DAN PERSEPSI KONSUMEN: IMPLIKASINYA TERHADAP KEBERLANJUTAN BISNIS - Yopita, Yopita; Putri, Fadillah Dwi (STMIK Pringsewu, 2024)
Green marketing has become one of the strategic approaches used by companies to support business sustainability efforts in the modern era. This concept refers to the implementation of environmentally friendly marketing practices, both in terms of products, production processes, and marketing communications to consumers. This study aims to explore consumer perceptions of green marketing and how the implementation of this strategy affects the sustainability of the company's business. The study uses a qualitative method with a literature analysis approach to understand consumer trends and perceptions in general from various previous studies. The results of the study indicate that effective green marketing can increase consumer loyalty, provided that consumers have a positive perception of the company's credibility and transparency in promoting environmentally friendly products. Negative perceptions, such as misleading green claims (greenwashing), can have a negative impact on the company's reputation and affect long-term business sustainability.